Mental Health in Transition : Assessment and Guidance for Strengthening Integration of Mental Health into Primary Health Care and Community-Based Service Platforms in Ukraine - World Bank Group (World Bank, Washington, DC, 2017)
Ukraine is undergoing important reforms in the health system, and there is an increasing interest among national as well as international actors in improving mental health services. The aim of this assessment is to provide recommendations to inform policy and operational guidance for strengthening integration of mental health into primary health care and community-based service platforms in Ukraine under the reform program.